2002
DOI: 10.1126/science.1069342
|View full text |Cite
|
Sign up to set email alerts
|

Noble Gas-Actinide Compounds: Complexation of the CUO Molecule by Ar, Kr, and Xe Atoms in Noble Gas Matrices

Abstract: The CUO molecule, formed from the reaction of laser-ablated U atoms with CO in a noble gas, exhibits very different stretching frequencies in a solid argon matrix [804.3 and 852.5 wave numbers (cm(-1))] than in a solid neon matrix (872.2 and 1047.3 cm(-1)). Related experiments in a matrix consisting of 1% argon in neon suggest that the argon atoms are interacting directly with the CUO molecule. Relativistic density functional calculations predict that CUO can bind directly to one argon atom (U-Ar = 3.16 angstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
201
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(220 citation statements)
references
References 25 publications
16
201
3
Order By: Relevance
“…Li et al suggested that this is due to a change in the electronic ground state, and presented density functional theory ͑DFT͒ calculations indicating that a weak bond arises by donation of electron density of the noble gas into the empty uranium 6d orbitals in CUO and UO 2 . 9,15 In argon and heavier noble gas matrices, this bonding interaction is strong enough to change the ordering of the ground and first excited states, leading to the observed strong redshifts. A convincing argument was the very good agreement between the calculated and observed asymmetric stretch frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al suggested that this is due to a change in the electronic ground state, and presented density functional theory ͑DFT͒ calculations indicating that a weak bond arises by donation of electron density of the noble gas into the empty uranium 6d orbitals in CUO and UO 2 . 9,15 In argon and heavier noble gas matrices, this bonding interaction is strong enough to change the ordering of the ground and first excited states, leading to the observed strong redshifts. A convincing argument was the very good agreement between the calculated and observed asymmetric stretch frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…A particularly interesting aspect is the interaction of small actinide molecules with noble gas matrices. Laser ablation spectroscopy has been used by Andrews and co-workers to trap UO, UO 2 , and CUO in noble gas matrices 3,[6][7][8][9][10][11][12][13][14][15] and measure vibrational frequencies as a function of the matrix composition ͑Ne, Ar, Kr, Xe, or mixtures thereof͒. An intriguing feature of both CUO and UO 2 is the large redshift ͑about 130 cm −1 ͒ in the antisymmetric stretch found when replacing a neon matrix by an argon matrix.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Of the new species the small CUO molecule has attracted much attention due to its remarkable behavior in different rare gas matrices. 3,4 Bringing laser ablated uranium atoms in contact with CO, the strong triple bond of the carbon monoxide is broken leaving CUO as the primary product of a reaction that also gives other secondary components like OUCCO. 5 Upon trapping the CUO molecule in different solid noble-gas ͑Ng͒ matrices Andrews and co-workers 6,7 found a large vibration frequency shift that could be explained by assuming that the ground state of the molecule is changed due to the interaction with the noble gas matrix: in neon the interaction is weak and the same singlet ground state is found as in the gas phase, whereas the stronger interaction with argon or krypton is sufficient to make the lowest lying triplet state the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…40 Since both the molecule of interest and the environment consist of neutral molecules, and because the dipole moments of the two states of interest of CUO do not differ much (3.5 D in the singlet state and 2.4 D in the excited triplet state 24 ), the most important factor is probably a combination of Pauli repulsion and weak coordination from the equatorial ligands. Most embedding methods are not able to capture such subtle effects as they are usually designed to describe primarily electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Again, a large red shift (≈70 and ≈200 cm −1 for the U-O and U-C stretching modes, respectively) was observed, relative to the data obtained in the neon matrix. [22][23][24] This large red shift in the vibrational spectra suggest that the ground-state of CUO depends on the noble gas environment, with the weakly interacting neon atoms the system favors a singlet ground-state while the stronger interaction in the heavier noble gas matrices, i.e., argon, krypton, or xenon, 23,25,26 produces a triplet ground-state in which also a nonbonding uranium 5f φ or 5f δ is occupied (or a mixture thereof if spin-orbit coupling is accounted for 17 ). Direct validation for this hypothesis could come from electronic spectroscopy on CUO in these matrices.…”
Section: Introductionmentioning
confidence: 99%